Development of a national automated endoscopy database: The United Kingdom National Endoscopy Database (NED). Issue 6 (July 2019) - Lee, Thomas JW; Siau, Keith; Esmaily, Shiran; Docherty, James; Stebbing, John; Brookes, Matthew J; Broughton, Raphael; Rogers, Peter; Dunckley, Paul; Rutter, Matthew D
Background: The National Endoscopy Database (NED) project commenced in 2013 under the auspices of the Joint Advisory Group. The aim is to upload endoscopy procedure data from all units across the United Kingdom to a centralised database. The database can be used to facilitate quality assurance, research and training in endoscopy. Objective: This article describes the development and implementation process of NED from its inception to date. Methods: NED utilises automated data uploading of a minimum dataset from local endoscopy reporting systems to a central national database via the internet. Currently all data are anonymised. Key performance indicators are presented to endoscopists and organisations on a web-based platform for quality assurance purposes. Results: As of October 2018, 295 endoscopy services out of a total of 529 known services in the UK (56%) are actively uploading to NED. Data from more than 400, 000 endoscopic procedures have been uploaded. Conclusion: UK-wide data collection from endoscopy units to a central database is feasible using an automated upload system. This has the potential to facilitate endoscopy quality assurance and research.